Assessment of surface phytoplankton in whale shark (Rhincodon typus) aggregation areas off Sogod Bay, Southern Leyte, Philippines during whale shark season of November 2017 to February 2018 - Jomadiao, Coleen Gail Yap; Yap-Dejeto, Leni G. (2022)
This study determined the phytoplankton community composition and diversity in the whale shark aggregation areas off Sogod Bay, Southern Leyte, from November 2017 to February 2018. Three stations were identified as whale shark aggregation areas and one station had no records of whale shark sightings. Physico-chemical parameters (temperature, pH, salinity, depth, turbidity, water current, and light intensity) were measured in situ. The phosphate, nitrate, and chlorophyll-a were analyzed in the lab.
Diatoms mostly comprised the whole shark aggregation areas, which were dominated by Skeletonema, Chaetoceros, Trichodesmium, Bacteriastrum, and Pseudonitzschia while dinoflagellates that dominated were Ceratium, Protoperidinium, Gymnodinium, Peridinium, and Gyrodinium. An average of 18 x 10 raised to the power of 3 cells/L was recorded for the whole sampling station. Average phytoplankton cell densities were recorded highest during the whale shark season, in February 2018, with 42 x 10 raised to the power of 3 cells/L, and lowest during November 2017, while whale sharks were feeding, at 7.7 x 10 raised to the power of 3 cells/L. Class Bacillariophyceae had the greatest relative cell density of 68.49%, while the least was Class Prymnesiophyceae with 0.02%. The highest diversity was recorded in Station 3 with H'= 2.525 and lowest in Station 2 with H'=1.701. There was a significant difference between the cell densities of the whale shark aggregation areas (23 x 10 raised to the power of 3 cells/L) and the non-whale shark aggregation area (5.6 x 10 raised to the power of 3 cells/L) with an F-value of 12.46 at .001 level of significance.
Undergraduate thesis (B.S. Biology) --University of the Philippines, Tacloban.
Keywords: Science and Technology